Local multipoint distribution services architecture based on rain profile extracted from meteorological radar [electronic resource] - Kusay Faisal A. Al-Tabatabaie, 1977- (2013)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2013